Variação espacial nas características da água, dos sedimentos e da macrofauna bentônica em áreas urbanizadas e em unidades de conservação na Baía da Ilha de Santa Catarina - Pagliosa, Paulo Roberto (2004)
Comparisons between urban and non-urban areas may be one method for the establishment of cause and effect relations in environmental changes provoked by urbanization in locations for which there is no historic data. The impacts of urbanization on water, sediment and the macrofaunal benthic associations were investigated using an hierarchized sample planning. The spatial variations were evaluated within a single estuary, within a single group of estuaries and between groups of urban and non-urban estuaries in the Santa Catarina Island Bay in southern Brazil. The properties of water, sediments and the benthic fauna were distinctly different between urban and non-urban areas. In the water (dissolved nutrients, particulated matter in suspension and phytoplankton biomass) and in the sediments (lead, zinc, and copper, phosphorus and polyphosphate) concentrations were higher and had greater variations in the urban estuaries than in the non-urban estuaries. In contrast, in the non-urban estuaries the concentrations were similar and often lower than those in the areas considered to be reference locations for biogeochemistry and ecotoxicology stu dies. The benthic fauna responded to the environmental changes in such a way that it can be separated in association with sensitive species, including Nephtys fluviatilis, Heteromastus similis and Kalliapseudes schubarti and in association with tolerant species, including the polychaete Laeonereis acuta and by a non-identified oligochaete Tubificidae. The study results indicate that in shallow coastal ecosystems the benthic and pelagic compartments are closely linked. Not only the changes in the characteristics of the sediments, but the water properties are also directly related to the changes in the fauna.